2014
DOI: 10.1093/jac/dku110
|View full text |Cite
|
Sign up to set email alerts
|

Secondary metabolism pathway polymorphisms and plasma efavirenz concentrations in HIV-infected adults with CYP2B6 slow metabolizer genotypes

Abstract: Among individuals with a CYP2B6 slow metabolizer genotype, CYP2A6 and possibly UGT2B7 polymorphisms contribute to even higher efavirenz concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 45 publications
3
56
2
Order By: Relevance
“…It is expected that the CYP2B6 variants evaluated in this study account for the majority of the influence of CYP2B6 genetic variability on efavirenz concentrations in the population studied, given the relatively low allelic frequency and/or minor effects of additional variants (28,35). In addition to CYP2B6, CYP2A6 polymorphisms have been shown to be associated with efavirenz CL/F, efavirenz concentrations, or 7-OH efavirenz concentrations (25,29,30). In these studies, the relative influence of the CYP2A6 genotypes on efavirenz PK was more prominent in CYP2B6 slow metabolizers, suggesting that the minor elimination pathway of 7-hydroxylation mediated by CYP2A6 may play an increased role in subjects with low CYP2B6 activity (20).…”
Section: Discussionmentioning
confidence: 91%
“…It is expected that the CYP2B6 variants evaluated in this study account for the majority of the influence of CYP2B6 genetic variability on efavirenz concentrations in the population studied, given the relatively low allelic frequency and/or minor effects of additional variants (28,35). In addition to CYP2B6, CYP2A6 polymorphisms have been shown to be associated with efavirenz CL/F, efavirenz concentrations, or 7-OH efavirenz concentrations (25,29,30). In these studies, the relative influence of the CYP2A6 genotypes on efavirenz PK was more prominent in CYP2B6 slow metabolizers, suggesting that the minor elimination pathway of 7-hydroxylation mediated by CYP2A6 may play an increased role in subjects with low CYP2B6 activity (20).…”
Section: Discussionmentioning
confidence: 91%
“…This was confirmed in a separate genomewide association study (GWAS) in 856 individuals that found no association between rs28399433 and estimated plasma trough concentrations of EFV [39]. However, when investigating only individuals with a CYP2B6 slow metabolizer genotype (defined by genotypes 516TT, or 516T/983C or 983CC of two SNPs rs3745274 and rs28399499) a significant association was observed between the CYP2A6 rs28399433 AC genotype and higher EFV plasma concentrations (as compared to AA genotype) [52]. The clinical relevance of this SNP on EFV treatment is unclear since no association with immunological failure, virologic response, or CNS toxicity has been reported (Table 2).…”
Section: Pharmacogeneticsmentioning
confidence: 82%
“…CYP2B6 516G > T, 983T > C, 785A > G and 21563C > T SNPs have been associated with greater efavirenz plasma exposure and the development of more severe central nervous system (CNS) effects in different HIV-infected populations, including African and Thai patients [39][40][41][42][43][44][45][46] . Likewise, increased efavirenz concentrations were associated with CYP2A6 -48T > G and with GG homozygosity for UGT2B7 735, a SNP of the microsomal enzyme uridine 5'-diphospho-glucuronosyltransferase (UGT), in Black and White, but not in Hispanic individuals from the United States [47] . Also, CYP2B6 *6/*6 and *6/*26 carriers have been found to be associated with extremely high plasma concentrations of efavirenz in Japanese patients receiving standard doses of the drug [48] .…”
Section: Nervous System Side Effectsmentioning
confidence: 99%